EFFECTIVENESS OF CRAB SNARES IN LABORATORY-SCALE TRIALS - Rihmi, Mihrobi Khalwatu; Sunardi, Sunardi; Fuad, Fuad (Directorate of Research and Community Service (DRPM), 2021)
The phenomenon of missing fishing gear during operation (Ghost fishing or Abandoned, lost or otherwise discarded fishing gear (ALDFG) becomes one of the serious problems in passive fishing gear. It's still a challenge and consensual for researchers to find the solution to solve this issue. This research is a steps of efforts to overcome it by using crab snares construction that has been used for recreational fishing activities. Crab snares consists of bait components and snaring rope. The research step consists of designing trap construction; selecting materials; building fishing gear; and conduct laboratory-scale trials. Then calculations of the effectiveness of the snare to catch crabs at various sizes. Observations during laboratory trials show that crab snares are capable of catching various sizes of crabs. Furthermore, the crabs caught were categorized into small, medium and large size groups based on their carapace width. analysis results of the effectiveness of catching snares show the highest value is 94.6% for catching large crabs, in the second position the effectiveness value is 86.4% for catching small crabs and the lowest is for catching medium crabs the effectiveness value still reaches 84.6%.